(3GdMSGe GdeMOhO aj GdQO Ydi GdjghOs - (3CHh eMeO YHO GdMb GdESdGej GdeZQHj GdSHJj, b (B8 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdeMehO Hcd dSGf GdeYHhO ai cd ReGf hSejJg GdMSGe GdeLQhO ai GdQO Ydi GdjghO GdHGH GdChd ai JbQjQ GdehGVY GdJi ai cJHge GdOGdI s
(3BNQgG (B:s
(3djchf GdeHJOi hGdefJgi hGf GdebUhO GdCYXe ef gPG GdJCdja hGNJe gPG Gdbhd HTcQ Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B_ (3GdeZQH (B(364 d) s
Keywords: (3GdeLGejYs